Occurrence of Acanthamoeba genotypes in Central West Malaysian environments - Basher, Mohamad Hafiz Abdul; Ithoi, Init; Mahmud, Rohela; Abdulsalam, Awatif Mohamed; Foead, Agus Iwan; Dawaki, Salwa; Atroosh, Wahib Mohammed Mohsen; Nissapatorn, Veeranoot; Abdullah, Wan Omar (Elsevier, 2018)
Acanthamoeba species are ubiquitous free-living protozoa that can be found worldwide. Occasionally, it can become parasitic and the causative agent of acanthamoebic keratitis (AK) and Granulomatous Amoebic Encephalitis (GAE) in man. A total of 160 environmental samples and 225 naturally-infected animal corneal swabs were collected for Acanthamoeba cultivation. Acanthamoeba was found to be high in samples collected from environments (85%, 136/160) compared to infected animal corneas (24.89%, 56/225) by microscopic examination. Analysis of nucleotide sequence of 18S rRNA gene of all the 192 cultivable Acanthamoeba isolates revealed 4 genotypes (T3, T4. T5 and T15) with T4 as the most prevalent (69.27%, 133/192) followed by T5 (20.31%), T15 (9.90%) and T3 (0.52%). Genotype T4 was from the strain of A. castellanii U07401 (44.27%), A. castellanii U07409 (20.83%) and A. polyphagaAY026243 (4.17%), but interestingly, only A. castellanii U07401 was detected in naturally infected corneal samples. In environmental samples, T4 was commonly detected in all samples including dry soil, dust, wet debris, wet soil and water. Among the T4, A. castellanii (U07409) strains were detected high occurrence in dry (45%) followed by aquatic (32.50%) and moist (22.50%) samples but however A. castellanii (U07401) strains were dominant in dry samples of soil and dust (93.10%). Subsequently, genotype T5 of A. lenticulata (U94741) strains were dominant in samples collected from aquatic environments (58.97%). In summary, A. castellanii (U07401) strains were found dominant in both environmental and corneal swab samples. Therefore, these strains are possibly the most virulent and dry soil or dusts are the most possible source of Acanthamoeba infection in cats and dogs corneas.